Acute renal infarct without apparent cause: A case report and review of the literature - Decoste, Ryan; Himmelman, Jeffrey G; Grantmyre, John (Canadian Urological Association Journal, 2015)
Acute renal infarction is a rare clinical entity most commonly occurring as a result of a thromboembolic event in patients with predisposing risk factors. Its non-specific presentation can lead to delayed or missed diagnosis. However, modern imaging technology has allowed for the diagnosis of renal infarction to be made earlier in its clinical course. Due to its rare nature, treatment guidelines do not exist. We report a case of acute renal infarction identified on computed tomography scan in a patient with no known predisposing factors to thromboembolism that was treated through suction thrombectomy.